ENERGYSAVING MANAGEMENT AND INCREASE OF TECHNICAL-ECONOMICAL EFFICIENCY OF PUMPINGS SETTINGS OF THERMAL AND ATOMIC POWER-STATIONS - Канюк, Геннадий Иванович; Мезеря, Андрей Юрьевич; Фокина, Анна Ростиславовна; Лаптинова, Екатерина Владимировна; Лаптинов, Иван Павлович (Eastern-European Journal of Enterprise Technologies, 2012)
In current article influence of technical descriptions of pumps is considered on the economy of power-stations. The algorithm of the optimum adjusting of frequency of pumps rotation is developed, thet`s providing the maximal value of general KPD of mechanism, principles of energysaving management the pumpings settings are considered.